Unregulated urban sprawl and spatial distribution of fire events: evidence from Greece. (20th October 2018) - Tsilimigkas, Georgios; Kizos, Thanasis; Gourgiotis, Anestis
ABSTRACT: Fire events are an annual phenomenon in Greece with damages and even casualties, making their understanding and management important. In this paper, we present fire events provided by NASA Fire Information for Resource Management System and place them along a number of spatial types defined by relief and land cover classes. Results demonstrate that the occurrence of fire events is related more to some land cover classes than others. The most important in terms of overall frequency in all types of terrain is 'Agricultural Areas', as a result of farming practices that involve fire. The second more important type of areas is 'Artificial Surfaces', especially in low lying areas. These events are related to urban growth and sprawl and are very often a direct outcome of speculation practices with land properties, encouraged by the absence or poor implementation of spatial planning.